From pixels to policy: deciphering G-20 countries’ digitalization, resource management, external conflicts, governance, and environmental frameworks - Liu, Qi; Mehmood, Usman (Frontiers in Environmental Science, 2025)
Due to economic growth, significant natural resource overuse and unsustainable use have hastened the adverse effects of excessive consumption, which has resulted in large increases in ecological footprint. Additionally, energy insecurity, increasing fossil fuel usage, and environmental unsustainability are significant challenges resulting from the escalating wars. However, resource consumption and environmental footprints may be impacted by the shift of energy systems and economic activity that promotes the use of clean energy and aids in the digitalization process. Thus, by incorporating external conflicts (EC) into the model, this study examines the effects of natural resources (NR), the digital economy (DIE), government stability (GOV), and clean energy (RE) on the ecological footprint (EF) in G-20 nations from 2000 to 2021. To provide panel estimates resistant to slope heterogeneity and cross-sectional dependence (CD), momentum quantile regression (MMQR) is used. The empirical findings show that the digital economy and natural resources are growing their economic footprints in the G-20 economies and are a major danger to the quality of the environment. The government and clean energy, however, contribute to a less ecological footprint. Furthermore, reducing disputes reduces ecological impact while improving economic conditions degrades environmental quality. These estimates serve as the foundation for comprehensive policies that enhance environmental quality through the energy transition, digitization, and sustainable use of natural resources.